Diagnóstico del potencial agroindustrial de la tara (Caesalpinia spinosa) en Cotopaxi - Alanuca Yanchatipán, Wilma Mariela (2017)
The objective of the present work is to determine the potential of the Tara (Caesalpinia spinosa) agroindustrial, a plant native to Peru but can be found from Venezuela, Colombia, Ecuador, Peru, Bolivia to northern Chile, in areas with a range of 4º- 32ºC, an average of 230 to 500mm of annual precipitation, being a leguminous species. The vegetal characteristics of this plant help the recovery of eroded soils; it is known that its fruit contains tannins, and rubber for industrial use. In the present investigation a random sampling of the existing species in the neighborhood Salache Bajo of the parish Eloy Alfaro, corner of Latacunga, province of Cotopaxi was proposed, to which a physical-chemical analysis of the pod was obtained obtaining as a result of the following Content Tannins 36.92%, moisture 14.20%, dry matter 85.80%, ash 2.39%, fat 0.59%, proteins 3.46%, crude fiber 10.24%, total carbohydrates 79.36 %, And energy 295, 65kcal / 100g. The analysis may conclude that vegetable tannin will be a possible substitute for chromium in the tannery process in the leather industry, which helps to reduce pollution of rivers and the environment, can also use gum or hydrocolloids as alternative product to the use of chemical stabilizers in the food industry.